2020
DOI: 10.31234/osf.io/jqus9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No more advantage for the home team: Refereeing without social pressure in European elite football during the COVID-19 pandemic. Draft version 3 30-03-2021

Abstract: Introduction. Due to the COVID-19 pandemic, European top football (soccer) leagues played the final rounds of season 2019/20 without or strongly limited attendance of supporters (i.e., “ghost games”). From a sport psychological perspective this situation poses a unique opportunity to investigate the crowd’s influence on sports professionals’ behavior and performance.Methods. A total of 1286 matches - played in the top leagues of Spain, England, Germany, Italy, Russia, Turkey, Austria and the Czech Republic - w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Other nations obtained less research as Portugal (14%), Austria (12%), North America (10%), Turkey (10%), France (8%) or Brazil, and 21 countries (Belgium, Scotland, Switzerland, Denmark, Sweden, Greece, Czech Republic, Albania, Romania, Hungary, Serbia, Slovenia, Poland, Ukraine, Russia, Israel, Egypt, Japan, China, Australia and Costa Rica) individually accounted for less than 5% each. Notably, 4 studies (8%) analyzed more than 8 (Leitner & Richlan, 2021a, 2021bMcCarrick et al, 2021;Sedeaud et al, 2021). Only one study not reported the analyzed countries (Webb, 2021).…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Other nations obtained less research as Portugal (14%), Austria (12%), North America (10%), Turkey (10%), France (8%) or Brazil, and 21 countries (Belgium, Scotland, Switzerland, Denmark, Sweden, Greece, Czech Republic, Albania, Romania, Hungary, Serbia, Slovenia, Poland, Ukraine, Russia, Israel, Egypt, Japan, China, Australia and Costa Rica) individually accounted for less than 5% each. Notably, 4 studies (8%) analyzed more than 8 (Leitner & Richlan, 2021a, 2021bMcCarrick et al, 2021;Sedeaud et al, 2021). Only one study not reported the analyzed countries (Webb, 2021).…”
Section: Descriptive Analysismentioning
confidence: 99%
“…It is interesting to point out that once the athletes returned to stadiums, another challenge appeared: the so-called ‘ghostly game’ (to play matches without the attendance of supporters, with empty tribunes). Certain researchers [ 26 ] took advantage of this once-in-a-lifetime opportunity to study the effects of public absence on the behavior of professional football players. The behavior of the Austrian players was analyzed and compared in 20 “ghosts’ games.” Marlovits [ 27 ] discovered that the most difficult challenge for players was “adapting to a non-resonant environment”.…”
Section: Introductionmentioning
confidence: 99%